Digital Government and Public Health - Jane E. Fountain (Centers for Disease Control and Prevention, 2004)
Digital government is typically defined as the production and delivery of information and services inside government and between government and the public using a range of information and communication technologies. Two types of government relationships with other entities are government-to-citizen and government-to-government relationships. Both offer opportunities and challenges. Assessment of a public health agencys readiness for digital government includes examination of technical, managerial, and political capabilities. Public health agencies are especially challenged by a lack of funding for technical infrastructure and expertise, by privacy and security issues, and by lack of Internet access for low-income and marginalized populations. Public health agencies understand the difficulties of working across agencies and levels of government, but the development of new, integrated e-programs will require more than technical change it will require a profound change in paradigm.